The role of eclogite in the rift-related metasomatism and Cenozoic magmatism of Northern Victoria Land, Antarctica - Melchiorre, Massimiliano; Coltorti, Massimo; Bonadiman, Costanza; Faccini, Barbara; O'Reilly, Suzanne Y.; Pearson, Norman J. (Lithos, 2011)
Sr, Nd, and Hf isotopic analyses of separated clinopyroxenes and in situ Re-Os isotopic analysis of sulphides in mantle-peridotite xenoliths from Baker Rocks (BR) and Greene Point (GP), less than 100. km apart in Northern Victoria Land (NVL), Antarctica, provide further constraints on the evolution of the sub-continental lithospheric mantle beneath NVL and suggest that eclogitic reservoirs may have played a role in the metasomatism and magmatism of the area.Most of the BR sulphides have radiogenic 187 Os/ 188 Os (0.1318-0.379 with 187 Re/ 188 Os ratios between 0.46 and 3.3), while unradiogenic 187 Os/ 188 Os characterizes the GP suite (0.1068-0.1279 with 187 Re/ 188 Os ratios from 0.0002 to 0.045). In BR silicates 87 Sr/ 86 Sr varies between 0.70296 and 0.70488, 143 Nd/ 144 Nd lies within a narrow range (0.51271-0.51296), and 176 Hf/ 177 Hf ranges from 0.28300 to 0.28337. Clinopyroxenes from GP have similar 87 Sr/ 86 Sr (0.70277 to 0.70434), 143 Nd/ 144 Nd between 0.51261 and 0.51347, and 176 Hf/ 177 Hf between 0.28332 and 0.28519.Notwithstanding the rather limited number of sulphides in the GP suite, Os model ages for BR and GP largely overlap. A histogram of T RD (Time of Rhenium Depletion) model ages shows peaks at 3.0-3.3Ga, 2.3Ga, 1.3-1.4Ga, 0.9-1.1Ga, 580-620Ma and 120Ma (the youngest being recorded only at BR). These ages fit reasonably well with the events that affected Antarctica during its geological evolution.The highly radiogenic Os found in the BR xenoliths can be explained through mixing with an eclogitic lithotype. Mafic magmas, now eclogite, may have been introduced into the sublithospheric NVL mantle during the Ross Orogeny (550-600. Ma) or older subduction events and reactivated during the opening of the West Antarctic Rift System. The mixing component will depend on the age of the subducted material. About 15% of recycled Archean material would be necessary in order to account for the most radiogenic Os-isotope values.Based on Hf systematics the most radiogenic Hf in the GP clinopyroxenes ...